Comparison of breathing rate in cross bred dairy cows across two seasons of highest and lowest temperature-humidity index as an indicator of thermal stress under the humid tropical climate - C. Ibraheem Kutty (Journal of Veterinary and Animal Sciences)
Understanding the variations of biomarkers in relation to weather parameters and biological indicators of thermal stress (TS) appears important to minimize the harmful consequences of climatic adversities on health and productivity of the animals. Hence, diurnal pattern of breathing rate (BR) among eight postpartum dairy cows were compared across two seasons of extreme THI variations. Association of BR with daily recording of weather parameters and weekly assessments of stress associated serum factors were analyzed to find out the usefulness of this basic biomarker in determining the extent of TS suffered by the animal. Highly significant (p